L-shaped association between triglyceride-glucose body mass index and short-term mortality in ICU patients with sepsis-associated acute kidney injury - Xu, Heping; Mo, Ruiyong; Liu, Yiqiao; Niu, Huan; Cai, Xiongwei; He, Ping (Frontiers in Medicine, 2024)
BackgroundSepsis is a systemic inflammatory response syndrome, with sepsis-associated acute kidney injury (SA-AKI) being a common complication. Insulin resistance (IR) is closely related to the stress response, inflammatory response, and severity of critical illness. The triglyceride-glucose body mass index (TyG-BMI) is a valuable tool for assessing IR. However, the relationships between TyG-BMI and clinical outcomes in patients with SA-AKI remain unclear.MethodsWe conducted a retrospective analysis of ICU patients with SA-AKI using data from the MIMIC-IV database. The Boruta algorithm was employed to select significant features for predicting short-term mortality in SA-AKI patients. Multivariate Cox proportional hazards regression, sensitivity analysis, restricted cubic spline (RCS) models, and Kaplan–Meier (K–M) survival analysis were used to assess the relationship between TyG-BMI and short-term mortality in SA-AKI patients. Subgroup analyses considered the effects of age, sex, ethnicity, comorbidities and septic shock.ResultsThis study included 3,349 patients, with males accounting for 60.5% of the patients. The Boruta analysis identified the TyG-BMI as an important clinical feature. Higher TyG-BMI values were significantly associated with reduced short-term mortality rates (28, 90, and 180 days) in patients with SA-AKI; for each standard deviation increase in TyG-BMI, the risk of all-cause death decreased by 0.2% (p < 0.0001). Kaplan–Meier analysis demonstrated that patients with high TyG-BMIs had significantly lower mortality rates than did those with low TyG-BMIs. The RCS model revealed an L-shaped nonlinear relationship between the TyG-BMI and mortality. Sensitivity analyses indicated that the association remained significant even after excluding patients with myocardial infarction, congestive heart failure, or those who were hospitalized in the ICU for less than 2 days. Subgroup analyses revealed a significant interaction effect on short-term mortality in CRRT patients (p < 0.05).ConclusionThe relationship between the TyG-BMI and short-term mortality in ICU patients with SA-AKI is significant, indicating its potential value for early risk assessment and clinical intervention.